1997
DOI: 10.1080/00014788.1997.9729553
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Choices, Environmental Uncertainty and SBU Performance: A Note on the Intervening Role of Management Accounting Systems

Abstract: This paper examines the role of management accounting systems (MAS) design on the relationship between: (1) strategic business unit (SBU) strategy and SBU performance and (2) perceived environmental uncertainty (PEU) on SBU performance. MAS design was defined in terms of the extent to which managers use broad scope MAS information for managerial decision making. The responses of 62 SBU managers, drawn from a crosssection of manufacturing companies in Western Australia, to a questionnaire survey were analysed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
159
3
30

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(211 citation statements)
references
References 45 publications
19
159
3
30
Order By: Relevance
“…In line with expectations, firms operating in higher PEU obtain higher benefit from contemporary MAPs (strategic management accounting and contemporary performance measures) than those operating in lower PEU. This is in line with the findings from previous research of Chenhall & Morris (1986), Gul & Chia (1994), Chong & Chong (1997), Agbejule (2005), and Abdel-Kader & Luther Table 6 Results of Kruskal-Wallis One-way ANOVA (Industry) Values in cells of pairwise comparisons are absolute actual differences while the values in parenthesis are critical differences.…”
Section: Discussion Of the Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…In line with expectations, firms operating in higher PEU obtain higher benefit from contemporary MAPs (strategic management accounting and contemporary performance measures) than those operating in lower PEU. This is in line with the findings from previous research of Chenhall & Morris (1986), Gul & Chia (1994), Chong & Chong (1997), Agbejule (2005), and Abdel-Kader & Luther Table 6 Results of Kruskal-Wallis One-way ANOVA (Industry) Values in cells of pairwise comparisons are absolute actual differences while the values in parenthesis are critical differences.…”
Section: Discussion Of the Findingssupporting
confidence: 90%
“…Many researchers examined the effect of PEU on the design of management accounting systems, and found that PEU has been associated with the usefulness of broad scope information. More specifically, additional information should be provided for managers facing high uncertainty in order to improve their decisions and firms' performance (Chenhall & Morris, 1986;Chong & Chong, 1997;Gordon & Narayanon, 1984;Gul & Chia, 1994). In other research, the moderator effect of PEU on the relationship between the use of management accounting system and managerial performance has been explored.…”
Section: Exogenous Factor: Perceived Environmental Uncertainty (Peu)mentioning
confidence: 99%
“…Environmental uncertainty is acknowledged to be one of the key contingency factors in MCS research (Chapman 1997;Chenhall 2003). For example, as Chong and Chong (1997) In order to operationalize environmental uncertainty, the measure of Govindarajan (1984) has been selected; containing one question for the respondent's perceived environmental uncertainty concerning eight different environmental influences. The measure is chosen due to its respondent-friendly structure and compactness compared to other measures such as in Miles and Snow (1978, p. 200) and Khandwalla (1972Khandwalla ( , 1977.…”
Section: Contingency Factors: External Characteristicsmentioning
confidence: 99%
“…incertidumbre percibida del entorno y sugieren técnicas e instrumentos contables más apropiados cuando el entorno competitivo es incierto (Duncan, 1972;Hofer, 1975;Hayes, 1977;Gordon & Narayanan, 1984;Govindarajan, 1984;Chenhall & Morris, 1986;Gul, 1991;Gul & Chia, 1994;Fisher, 1995;Chong, 1996;Chong & Chong, 1997;Chapman, 1997;Kasurinen, 2002;Chenhall, 2003;Fuentes, 2003;Wenisch, 2004;Banker et al, 2004;Hoque, 2004Hoque, , 2005Agbejule, 2005;Jusoh, 2008;Hendricks et al, 2012;Jacomossi & Silva, 2016).…”
Section: Incertidumbre Percibida Del Entornounclassified